Differential Role of Components of the Fibrinolytic System in the Formation and Removal of Thrombus Induced by Endothelial Injury - Matsuno, Hiroyuki; Kozawa, Osamu; Niwa, Masayuki; Ueshima, Shigeru; Matsuo, Osamu; Collen, Désiré; Uematsu, Toshihiko (Thrombosis and Haemostasis, 1999)
The role of fibrinolytic system components in thrombus formation and removal in vivo was investigated in groups of six mice deficient in urokinase-type plasminogen activator (u-PA), tissue-type plasminogen activator (t-PA), or plasminogen activator inhibitor-1 (PAI-1) (u-PA-/-, t-PA-/- or PAI-1-/-, respectively) or of their wild type controls (u-PA+/+, t-PA+/+ or PAI-1+/+). Thrombus was induced in the murine carotid artery by endothelial injury using the photochemical reaction between rose bengal and green light (540 nm). Blood flow was continuously monitored for 90 min on day 0 and for 20 min on days 1, 2 and 3. The times to occlusion after the initiation of endothelial injury in u-PA+/+, t-PA+/+ or PAI-1+/+ mice were 9.4 ± 1.3, 9.8 ± 1.1 or 9.7 ± 1.6 min, respectively. u-PA-/- and t-PA-/- mice were indistinguishable from controls, whereas that of PAI-1-/- mice were significantly prolonged (18.4 ± 3.7 min). Occlusion persisted for the initial 90 min observation period in 10 of 18 wild type mice and was followed by cyclic reflow and reocclusion in the remaining 8 mice. At day 1, persistent occlusion was observed in 1 wild type mouse, 8 mice had cyclic reflow and reocclusion and 9 mice had persistent reflow. At day 2, all injured arteries had persistent reflow. Persistent occlusion for 90 min on day 0 was observed in 3 u-PA-/-, in all t-PA-/- mice at day 1 and in 2 of the t-PA-/-mice at day 2 (p <0.01 versus wild type mice). Persistent patency was observed in all PAI-1-/- mice at day 1 and in 5 of the 6 u-PA-/- mice at day 2 (both p <0.05 versus wild type mice). In conclusion, t-PA increases the rate of clot lysis after endothelial injury, PAI-1 reduces the time to occlusion and delays clot lysis, whereas u-PA has little effect on thrombus formation and spontaneous lysis.